Familial Mediterranean fever in Russia: Experience of the Federal Rheumatology Center - E. S. Fedorov; S. O. Salugina; N. N. Kuzmina (Современная ревматология, 2017)
The paper gives the experience of the V.A. Nasonova Research Institute of Rheumatology in identifying and managing patients with familial Mediterranean fever (FMF). Objective: to describe the features of the disease in patients with FMF in Russia and to compare them with the data obtained in the study of Turkish and Armenian populations with a high incidence of this disease. Patients and methods. The investigation enrolled 23 patients with a documented diagnosis of FMF who met the Turkish pediatric criteria (F. Yalcinkaya et al.) and/or the criteria described by A. Livnech et al. and had two identical mutations (homozygosity) or two different mutations (compound heterozygosity) in the MEFV gene. Among the patients there were 9 men and 14 women. The age of the patients at the time of treatment was 4.5 to 36 years. Their age at onset of FMF was 2 months to 15 years (mean age, 3.2±2.3 years). Results. The examination established that 18 (78.3%) patients were Armenians, 3 were representatives of the North Caucasus peoples (a Darghin woman, an Avar man, and an Ingush/Kabardian man), a man from mixed (Greek/Georgian) marriage, and a Russian woman whose ancestors were Armenian and Jewish. The most common manifestation of FMF were recurrent episodes of fever (22; 95.7%); abdominal pain with fever ranked second (19; 82.6%), followed by chest pain (11; 47.8%), locomotor apparatus lesion (16; 69.6%), and skin lesions (7; 30.4%). The episodes were accompanied by increased levels of acutephase markers in 100% of the patients. There were a high proportion of patients, in whom FMF was concurrent with other rheumatic and autoinflammatory diseases (juvenile chronic arthritis, chronic recurrent multifocal osteomyelitis, and acute rheumatic fever) (7; 30.4%). Twenty-two (95.6%) patients received colchicine; the tumor necrosis factor inhibitor etanercept was prescribed in 2 (8.7%) patients with comorbidity; there was a pronounced therapeutic effect. Conclusion. Although the majority of our patients were Armenians, the disease was also identified in those belonging to the peoples of the North Caucasus and Transcaucasia and in one Russian female patient. There has generally been a fairly typical picture of the disease. The considerable frequency of joint damage and the high proportion of patients with comorbid rheumatic diseases have engaged our attention. From a diagnostic point of view, of importance is the elevated level of acutephase markers during a disease attack, which in combination with the clinical and ethnic characteristics of patients allows the diagnosis of FMF to be suspected.